2006
DOI: 10.1093/toxsci/kfl044
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic Biotransformation and Metabolite Profile during a 2-Week Depuration Period in Atlantic Salmon Fed Graded Levels of the Synthetic Antioxidant, Ethoxyquin

Abstract: The synthetic antioxidant ethoxyquin (EQ) is increasingly used in animal feeds and has been candidate for carcinogenicity testing. EQ has the potential for toxicological and adverse health effects for both fish and fish consumers through "carryover" processes. The toxicological aspects of EQ have not been systematically investigated. The present study was performed to investigate the hepatic metabolism, metabolite characterization, and toxicological aspects of EQ in salmon during a 2-week depuration after a 12… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 57 publications
0
17
0
Order By: Relevance
“…We propose that compounds esterified at the 6-oxygen atom are hydrolyzed rapidly by trypanosomal esterases, followed by two-electron oxidation to a quinone imine species. 28,45 This quinone imine could then undergo a single electron reduction to form a semiquinone that may enhance the rate of formation of reactive oxygen species such as superoxide and/or other free radicals. 46,47 The added strain on the parasite's antioxidant machinery could lead to lethal consequences for the organism (see Scheme 6).…”
Section: Discussionmentioning
confidence: 99%
“…We propose that compounds esterified at the 6-oxygen atom are hydrolyzed rapidly by trypanosomal esterases, followed by two-electron oxidation to a quinone imine species. 28,45 This quinone imine could then undergo a single electron reduction to form a semiquinone that may enhance the rate of formation of reactive oxygen species such as superoxide and/or other free radicals. 46,47 The added strain on the parasite's antioxidant machinery could lead to lethal consequences for the organism (see Scheme 6).…”
Section: Discussionmentioning
confidence: 99%
“…PCR primers for amplification of 76-146 bp gene-specific PCR-products were designed from conserved regions of the studied genes. The primer sequences, their amplicon size, and the optimal annealing temperatures are shown in Table 3 and were performed according to established methods in our laboratory (17,24). Sequences were confirmed using NCBI nucleotide BLAST software (http://www.ncbi.nlm.nih.gov/BLAST).…”
Section: Methodsmentioning
confidence: 99%
“…It was in agreement with the results obtained earlier by Skaare and Roald [ 27 ]. EQ is considered as a model inducer of phase II enzymes involved in the metabolism of xenobiotics, but influence of EQ on phase I enzyme gene transcript levels was also observed [ 28 , 29 ]. The key role in mediating phase I reactions (e.g., oxidation or reduction) producing more hydrophilic compounds is played by the CYP (cytochrome P450) enzyme family.…”
Section: Biotransformation Of Eqmentioning
confidence: 99%
“…The key role in mediating phase I reactions (e.g., oxidation or reduction) producing more hydrophilic compounds is played by the CYP (cytochrome P450) enzyme family. Bohne et al [ 28 , 29 ] observed the alteration of CYP3A gene expression; an increase in the amount of CYP3A transcripts was detected in salmon after feeding them with the diet containing EQ at the highest dose used (1800 mg kg −1 ). The authors speculate that EQ may regulate CYP3 gene expression by interaction, for example, with pregnane X nuclear receptor (PXR) whose function is to sense the presence of toxic xenobiotics and in response enhance the expression of proteins involved in their detoxification.…”
Section: Biotransformation Of Eqmentioning
confidence: 99%